Tools for Online Tutors: A Review of the Effectiveness of the Student Tracking Facility in One Blackboard Classroom - Hewling, Anne (Proceedings of the International Conference on Networked Learning, 2004)
This brief paper examines the potential of platform based student tracking tools to assist online tutors in monitoring the learning activity of their students. It makes particular reference to a group of students working within one Blackboard mediated classroom by examining how actual behaviour correlated with that monitored automatically by the delivery platform. It concludes that whilst student tracking can be a useful tool in certain circumstances, reliance on it as the sole means of monitoring student participation and learning is unsound.